Analysis of Factors Influencing Consumer Behavior in Choosing Services : A Case Study of Ivan Gunawan's Mandjha Hijab Company in Central Java - sapto supriyanto; Bambang Guritno; Samtono (Badan Penerbit STIEPARI Press, 2025)
This study analyzes consumer behavior in purchasing hijab products from the Mandjha by Ivan Gunawan brand by examining the influence of product quality, price, promotion, and store location. The background of this research lies in the rapid development of the Muslim fashion industry in Indonesia, which has led to increasing competition among local hijab brands. The key issue explored is what factors most significantly influence consumer decisions to purchase Mandjha products. A qualitative descriptive method was used, involving interviews, observations, and documentation with selected consumers and marketing staff. The research identifies how consumers respond to various marketing elements implemented by the brand. Findings show that product quality—including fabric comfort, trendy design, and an exclusive image—remains the most influential factor in the buying decision. While the price reflects the quality and branding, it can be a limiting factor for some segments. Promotional strategies, especially through social media and celebrity endorsements, effectively increase brand awareness and emotional engagement, particularly among millennial consumers. Store accessibility and strategic locations also positively influence purchasing decisions, though to a lesser extent than product and promotion. Consumer behavior toward Mandjha products appears to be driven by a mix of rational considerations (price and quality) and emotional connections (branding and promotion). This dual influence suggests that companies should adopt an integrated marketing approach to build strong brand loyalty and sustain competitiveness. The study concludes that focusing on continuous product development, strategic pricing, creative promotional techniques, and accessible store placement is essential for maintaining consumer interest. It also recommends further research with quantitative methods and a larger, more diverse sample to validate and expand the findings.